The Crime of Self‐Solicitation. (June 2015) - Sachs, Benjamin
Abstract I hold that we could justifiably criminalize some threats, on account of the fact that issuing them renders one more likely to commit a crime. But I also point out that if we criminalize some threat‐issuing, we will de facto criminalize some warning‐issuing, which is unjust. So we ought not to criminalize any threat‐issuing. Instead, we should criminalize (roughly) rendering oneself more likely to commit a crime. This would allow us to punish all the threat‐issuers we should want to punish. It would also force us to punish some warning‐issuers, but we would not be punishing them for their warning‐issuing.